Ab initio study of C14 laves phases in Fe-based systems - Pavlu J. (Journal of Mining and Metallurgy. Section B: Metallurgy, 2012)
Structural properties and energetics of Fe-based C14 Laves phases at various compositions (i.e. Fe2Fe, Fe2X, X2Fe, X2X, where X stands for Si, Cr, Mo, W, Ta) were investigated using the pseudopotential VASP (Vienna Ab initio Simulation Package) code employing the PAW-PBE (Projector Augmented Wave - Perdew Burke-Ernzerhof) pseudopotentials. Full relaxation was performed for all structures studied including the reference states of elemental constituents and the equilibrium structure parameters as well as bulk moduli were found. The structure parameters of experimentally found structures were very well reproduced by our calculations. It was also found that the lattice parameters and volumes of the unit cell decrease with increasing molar fraction of iron. Thermodynamic analysis shows that the Fe2X configurations of Laves phases are more stable than the X2Fe ones. Some of the X2Fe configurations are even unstable with respect to the weighted average of the Laves phases of elemental constituents. Our calculations predict the stability of Fe2Ta. On the other hand, Fe2Mo and Fe2W are slightly unstable (3.19 and 0.68 kJ.mol-1, respectively) and hypothetical structures Fe2Cr and Fe2Si are found unstable as well.